Are terrestrial isopods able to use stridulation and vibrational communication as forms of intra and interspecific signaling and defense strategies as insects do? A preliminary study in Armadillo officinalis - Cividini, Sofia; Sfenthourakis, Spyros; Montesanto, Giuseppe (Die Naturwissenschaften, 2020)
The capability of producing sounds and vibrations is well known in insects and is thought to be a form of intra- and interspecific communication. Sounds and vibrations are used and modulated for several aims such as interacting with conspecifics, getting information from the environment, and defending against predators. This phenomenon is less known but also present in other arthropods, including a few roller-type terrestrial isopods. In this study, we used a Y-shape test apparatus to investigate the behavior of adult individuals of Armadillo officinalis Duméril, 1816 (Crustacea: Isopoda: Oniscidea) when exposed to two particular vibrational stimuli, namely species-specific stridulations and non-specific substrate-borne vibrations. Our results showed that adults of A. officinalis significantly react to the presence of both types of vibrational stimuli, by moving away from the vibrational source as if they experienced these vibrations as a sign of danger or disturbance. A. officinalis can produce stridulations only when it rolls into a ball during the so-called conglobation, a possible defense mechanism against predators. Stridulation might thus be a secondary form of defense used during conglobation to deter a predator following contact with it and might be experienced as an alert by conspecifics nearby. The high sensitivity to non-specific substrate-borne vibrations might provide A. officinalis with the possibility to anticipate dangers and adverse conditions, giving it a better chance of survival.